Pengaruh Perkembangan Filsafat Ilmu terhadap Ilmu Pengetahuan Kontemporer - Intan Dwi Rahayu (Yayasan Azzuhri Lengkok Lombok Timur, 2023)
Abstract Penelitian ini bertujuan untuk menganalisis dampak yang signifikan dari This research aims to analyze the significant impact of the development of the philosophy of science on contemporary science. Philosophy of science has long been a conceptual basis for understanding scientific epistemology, methodology and ethics. In this context, this research traces the evolution of the philosophy of science from classical thought to the modern era and how these views shape and influence the science we have today. The research method used involves analysis of historical and philosophical literature, highlighting the thoughts of influential philosophers of science such as Plato, Aristotle, Francis Bacon, Thomas Kuhn, Karl Popper, and other important figures. This research also considers developments in the philosophy of science, such as positivism, postmodernism, and feminist thought, as well as the ways in which these views have influenced research methodology, epistemological understanding, and contemporary scientific practice. The results of this research reveal that the philosophy of science has played an important role in the formation of scientific paradigms, the development of scientific theories, as well as in the development of more reflective and ethical research practices. The impact of the philosophy of science is also reflected in the research ethics controversies and fundamental questions about the nature of science that continue to be debated in scientific society today. This research provides a deeper understanding of the close relationship between philosophy of science and contemporary science, and underlines the importance of philosophical awareness in developing better and more responsible knowledge. These findings may provide a foundation for further developments in deep philosophical thinking about science and future scientific research. Keywords: philosophy of science, science, contemporary